Case Report: Local anesthetic systemic toxicity during regional anesthesia in a patient with rheumatoid arthritis - Baic, Misa; Milenovic, Miodrag; Obradovic, Danilo; Lukic, Relja; Dragovic, Gordana; Obradovic, Bozana (Frontiers in Medicine, 2026)
BackgroundLocal anesthetic systemic toxicity (LAST) is a rare yet potentially life-threatening complication that requires prompt recognition and management. This condition commonly presents with manifestations that involve both the central nervous system (CNS) and the cardiovascular system (CVS). While LAST occurs infrequently during peripheral nerve blocks, its consequences can be severe if left unrecognized.Case presentationThis article presents a case involving CNS manifestations of LAST in a patient with rheumatoid arthritis (RA). The patient was a 69-year-old female individual who was admitted for evaluation and treatment of a distal radius fracture previously managed at another healthcare facility and subsequently underwent open reduction and internal fixation (ORIF) at our institution. We propose that RA may constitute an additional risk factor for LAST development due to disease-associated alterations in vascular permeability.ConclusionOlder patients with rheumatoid arthritis may be at increased risk for LAST due to disease-related vascular permeability changes, showing the need for increased vigilance during the administration of regional anesthesia. Early diagnosis and timely administration of intravenous lipid emulsion (ILE) remain critical for the successful management of this potentially life-threatening complication.